ARE YOU CONTROLLING YOUR E-MAIL? OR IS YOUR E-MAIL CONTROLLING YOU? - Eldridge, John (Iated-Int Assoc Technology Education & Development, 2013)
As we all know, communications have and are going through a global revolution. It is just over 40 years since the first 'e-mail' was sent; now, it is estimated that corporate e-mail traffic amounts to some 86 billion e-mails per year. This has changed the entire way we work, with estimates again suggesting that around 28% of corporate time is now spent on e-mail, and that an average corporate user may be sending and receiving over 100 e-mails a day. Since e-mail is used both socially and professionally conventions and expectations regarding e-mail use have become somewhat blurred, and most users will report cases of frustration, upset, time-wasting and miscommunication through the medium. An understanding of e-mail behavior, and the development of e-mail skills would therefore seem to be essential for organizations, and a key component of educational programmes, including second language teaching programmes. This paper therefore focuses on e-mail waste, e-mail quality, and e-mail education from both a business and a linguistic perspective.
6th International Conference on Education, Research and Innovation (ICERI) -- NOV 18-20, 2013 -- Seville, SPAIN